(untitled) (The Lumbini Journal of Business and Economics, 2023)
This study aims to find the effect of banking depth on economic growth of South Asian countries. For analysis, different models are selected based on different tests (BP tests, Hausman tests) rather depending solely on the possible theoretical explanations. Six SAARC countries are selected for the study with data ranging from 1983-2020. The findings conclude negative and positive significant effect of credit flow to private sector and broad money respectively. Overall, banking depth has significant effect on GDP of SAARC nations. Meanwhile, gross domestic savings have significant positive contribution to GDP growth, whereas; inflation and gross capital formation negatively and positively insignificantly impact the economic growth respectively. These insignificances show the weakness of the economy in utilizing the credit and capital in the productive sectors of the economy. It further adds empirical evidence to existing finance-growth nexus in SAARC nations.